One Model, Two Enzymes: Activation of Hydrogen and Carbon Monoxide. (23rd June 2017) - Ogo, Seiji; Mori, Yuki; Ando, Tatsuya; Matsumoto, Takahiro; Yatabe, Takeshi; Yoon, Ki‐Seok; Hayashi, Hideki; Asano, Masashi
Abstract: The ability to catalyze the oxidation of both H2 and CO in one reaction pot would be a major boon to hydrogen technology since CO is a consistent contaminant of H2 supplies. Here, we report just such a catalyst, with the ability to catalyze the oxidation of either or both H2 and CO, based on the pH value. This catalyst is based on a NiIr core that mimics the chemical function of [NiFe]hydrogenase in acidic media (pH 4–7) and carbon monoxide dehydrogenase in basic media (pH 7–10). We have applied this catalyst in a demonstration fuel cell using H2, CO, and H2 /CO (1/1) feeds as fuels for oxidation at the anode. The power density of the fuel cell depends on the pH value in the media of the fuel cell and shows a similar pH dependence in a flask. We have isolated and characterized all intermediates in our proposed catalytic cycles.